Respuesta :
Answer:
1)
[tex]5 + 9 \div 3 - 1 = 7[/tex]
2) Find the Equivalent Expression ?
[tex]5(x - 1) + 7 = 5(x) + 5( - 1) + 7[/tex]
[tex] = 5x - 5 + 7[/tex]
[tex] = 5x + 2[/tex]
[tex]\huge{\underline{\underline{\boxed{\sf{\green{ǫᴜᴇsᴛɪᴏɴ}}}}}}[/tex]
- 5 + 9 ÷ 3 -1 = ???
[tex]\large\huge\green{\sf{Answer:-}}[/tex]
- 7 is correct answer
[tex]\huge{\underline{\underline{\boxed{\sf{\green{Explanation:-}}}}}}[/tex]
[tex] \red {\mathbb{ \underline { \tt By \: using \: BODMAS \: Rule}}}[/tex]
➡5 + 9 ÷ 3 -1
= 5+3 -1
= 8-1
= 7
:)